(untitled) (Philosophy and Progress, 2023)
In the course of his groundbreaking work, The Wretched of the Earth, Frantz Fanon has employed a splendid array of metaphors to reflect on the essential fabric of a colonized society. However, the Manichean metaphor is the best of them, which he has used to forge a comparison between colonialism and Manichaeism, a dualistic religious movement founded in ancient Persia sometime during the third century CE. This metaphor is singular in the sense that both colonialism and Manichaeism have in common a dichotomic vision to look at the world, a stupendous effort to exert their influences on the better part of the world and a messianic zeal to preach their enlightenment values at every opportunity. In this article, I am going to elucidate the way Fanon has made use of the metaphor to designate the identity formation of both the colonizer and the colonized in addition to critically analysing their similitude in vision, will and enthusiasm. In so doing, I will bring into play the recent accretions of Manichean religious and postcolonial studies in order to situate Frantz Fanon’s The Wretched of the Earth in the framework of post-colonial praxis. Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 153-177